2008
DOI: 10.1177/1721727x0800600203
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Molecules and Their Diffusion across Human Vaginal Mucosa

Abstract: The diffusion rate of permeant molecules through mucosal tissue depends on the physicochemical characteristics of the molecules themselves as well as the properties of the tissue. In this study the diffusion kinetics of various molecules was examined through intact as well as de-epithelialised human vaginal mucosa. The molecules studied included tritium-labelled water, 17β-estradiol, reduced-arecoline, vasopressin, oxytocin, bradykinin, tacrolimus, cyclosporin A, dihydro-alprenolol, cimetidine and benzylpenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Previous studies on the diffusibility of various compounds across vaginal mucosa indicated that charged tertiary amines in a molecule may interact extensively with intercellular negative charges of the epithelial barrier. 31 Because azithromycin contains 1 extra hydrogen bonding group and 1 extra N atom, which enable its interaction with other charged groups in the membrane barrier, its diffusion rate is likely to be retarded as compared with clarithromycin. Because aqueous solutions of any topically applied drug are readily removed from the surface of the eye by the tears and normal blinking, more viscous depot formulations can be used to prolong the contact time of the drug on the eye surface.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the diffusibility of various compounds across vaginal mucosa indicated that charged tertiary amines in a molecule may interact extensively with intercellular negative charges of the epithelial barrier. 31 Because azithromycin contains 1 extra hydrogen bonding group and 1 extra N atom, which enable its interaction with other charged groups in the membrane barrier, its diffusion rate is likely to be retarded as compared with clarithromycin. Because aqueous solutions of any topically applied drug are readily removed from the surface of the eye by the tears and normal blinking, more viscous depot formulations can be used to prolong the contact time of the drug on the eye surface.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the physicochemical nature of a drug also determines the pathway of drug diffusion. Bradykinin, being hydrophilic, diffuses through the paracellular pathway and its diffusion across the vaginal epithelial cells is retarded due to the interaction between the negatively charged epithelium and two positively charged arginine groups in bradykinin, suggesting that the drug–drug molecule charge is also a factor impacting drug absorption [ 83 ]. This could indeed be a basis to discriminate various molecules for desired local versus systemic effects [ 5 ].…”
Section: Vaginal Drug Delivery Systems: History and Present Therapeuticsmentioning
confidence: 99%
“…An interesting case in point is where the vaginal distribution and retention of doxorubicin (DXN) was increased by formulating hypotonic mucoinert nanoparticles. Here, the hypotonicity resulted in epithelial cells absorbing extracellular fluid to help revert to an isotonic state, and this influx of water carried DXN, alongside water, into cells [ 83 , 85 ]. These examples illustrate the value and important role that excipients play in attaining optimal drug absorption and retention, an aspect that is extensively explored in later sections.…”
Section: Vaginal Drug Delivery Systems: History and Present Therapeuticsmentioning
confidence: 99%
“…That the weakly basic DPV molecule exists predominately in its protonated form (DPV-H + ) at normal healthy acidic vaginal pH may explain its relatively low systemic absorption following vaginal administration [51][52][53]. A small number of previous studies have sought to determine whether the principles of pH partition theory-which have been widely considered and are well established for intestinal drug absorption-also apply to ionisable drugs administered vaginally [49,[54][55][56][57][58]. It would be interesting to assess whether vaginal pH impacts DPV systemic absorption in the clinic, particularly given the very high prevalence of bacterial vaginosis among women in sub-Saharan Africa, where the DPV ring is intended for use [59][60][61].…”
Section: In Vitro Release Testing Of Rings Using a Two-phase Buffer/octanol Systemmentioning
confidence: 99%